1999
DOI: 10.1038/sj.bjc.6690300
|View full text |Cite
|
Sign up to set email alerts
|

Second malignant neoplasms after a first cancer in childhood: temporal pattern of risk according to type of treatment

Abstract: SummaryThe variation in the risk of solid second malignant neoplasms (SMN) with time since first cancer during childhood has been previously reported. However, no study has been performed that controls for the distribution of radiation dose and the aggressiveness of past chemotherapy, which could be responsible for the observed temporal variation of the risk. The purpose of this study was to investigate the influence of the treatment on the long-term pattern of the incidence of solid SMN after a first cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
3
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 23 publications
5
94
3
9
Order By: Relevance
“…In general, the combined carcinogenic risk has been found to be greater than additive (Travis et al, 1996;de Vathaire et al, 1999;Garwicz et al, 2000), although this…”
Section: Introductionmentioning
confidence: 92%
“…In general, the combined carcinogenic risk has been found to be greater than additive (Travis et al, 1996;de Vathaire et al, 1999;Garwicz et al, 2000), although this…”
Section: Introductionmentioning
confidence: 92%
“…10 Thyroid cancer has been frequently reported as a SPN after treatment for childhood cancers including Hodgkin's disease, neuroblastoma and other malignancies that involve radiation to the neck region. [11][12][13] We carried out a cohort study to determine the overall risk of developing a thyroid SPN in 5-year childhood cancer survivors in the British Childhood Cancer Survivor Study (BCCSS).…”
mentioning
confidence: 99%
“…In the same study the risk increased with the number of ChT cycles of ChT with AA or platinum agents as well. Besides that, it is reported that CCS treated for Ewing sarcoma, Hodgkin lymphoma and bilateral retinoblastoma are at the highest risk for SPN [5,13]. Our patient got SPC after a relatively long latency period of 28 years after treatment for Ewing sarcoma.…”
Section: Discussionmentioning
confidence: 81%